The art of walking in nature - Grundmann, María José Arbeláez (Revista do Colóquio, 2021)
The art of walking in nature revolves around the ethics and politics of how we humans relate to nature when we walk paths. The answer is nourished by the spiritual ecofeminist philosophy of Vandana Shiva, which considers, together with indigenous communities, the earth as a living being, with which man has a spiritual connection and is not only the guarantor of its existence through unlimited exploitation. The reflection on the ways in which man relates to the community of living beings is expanded through the proposal of the ethics of the earth developed by Carlos Alfredo Vargas. As an artistic practice and research project, the art of walking is a conscious daily living experience in walking different paths, during which relationships of various kinds are established, exploring creative processes from bodily sensations thanks to the walker's openness to the untimely forces that traverse and modify his body, taking as a reference the "body without organs", a category developed by (Deleuze; Guattari). Walking through different territories allows for the symbolic resignification of places, without needing to be expressed in materialities; on the contrary, this practice is so respectful that it only leaves mobile and evanescent traces.